TINJAUAN KECEMASAN DAN MOTIVASI ATLET EKSTRAKURIKULER SEBELUM MENGIKUTI PERTANDINGAN BULUTANGKIS MAS TI PASAR SURIAN - Putra Mulyawan, Muhammad Raja Asratullah; Haw Sin, Tjung; Mardesia, Pringgo; Edmizal, Eval (Fakultas Ilmu Keolahragaan Unimed, 2025)
This study aims to determine the anxiety and motivation levels of MAS TI Pasar Surian badminton extracurricular athletes before participating in competitions. Anxiety and motivation are psychological factors that have a significant effect on athletes' mental readiness and performance in competitions. This study uses a descriptive method with a quantitative approach. The population in this study consisted of all 30 extracurricular badminton athletes at MAS TI Pasar Surian. The sampling technique used total sampling, so that the entire population was used as the research sample. Data collection was conducted through questionnaires, which were then analysed using the frequency distribution technique with the percentage formula P = F/N × 100%. The results showed that the athletes' anxiety levels were in the moderate to high categories, with 3 people (10%) in the very low category, 3 people (10%) in the low category, 12 people (40%) in the moderate category, 6 people (20%) in the high category, and 6 people (20%) in the very high category. Meanwhile, the athletes' motivation levels tended to be low, with 3 people (10%) in the very low category, 14 people (46.7%) in the low category, 10 people (33.3%) in the moderate category, 1 person (3.3%) in the high category, and 2 people (6.7%) in the very high category. These results indicate that most athletes still experience high anxiety and low motivation ahead of competitions, necessitating intensive mental and motivational coaching by trainers to enhance athletes' readiness and performance.